Estudo sobre representações sociais de casamento e práticas conjugais para nipo-descendentes e brasileiros - Waricoda, Ana Sayuri Ribeiro (2010)
One hundred years after the arrival of the first Japanese’s immigrants in Brazil, their descendants constitute a portion of the Brazilian population receiving Occidental cultural influences, but also share peculiar Japanese customs and values. This research intended to know by the Theory of Social Representations and Theories of Gender, how conceptions of marriage and love can be affected by cultural influences between Brazilian and JapaneseBrazilian, and thus understand more about the universe of Brazilian and Japanese culture for these people. Therefore, 100 women and men participants, Brazilian and JapaneseBrazilian, answered an evocation questionnaire containing the terms inducers marriage and love, and has used the software EVOC for processing the data. Then we interviewed eight participants, four men and four women, Nikkei, about marital history and everyday life. For processing data collected in interviews applied technique of analysis Content. The results indicate social representations based on traditional models of marital and love, but they have in peripheral elements that indicate the influence of love-romantic and individualism that can collaborate with a change of conception. As practices identified in participants' reports, they reveal relationships mainly influenced by an individualistic vision, in that spending and household tasks are shared by both sexes in marriage. However, there is in the women discourse a hard time men in accepting this division, while for the men interviewed, the division is a reality.